Effect of pre-incubation long-term storage and warming on hatchability of Japanese quail eggs (Coturnix coturnix japonica) - Seker, I; Bayraktar, M; Kul, S (Eugen Ulmer Gmbh Co, 2006)
The objective of the present study was to investigate the effects of warming of Japanese quail eggs at the beginning and during the long-term storage on embryonic mortality and hatchability of fertile eggs. A total of 2700 Japanese quail eggs were used for this study. The eggs were collected from 20-week-old laying quails for each trial for 3 consecutive days. The birds were housed as 1 male/3 female per cage of 40x30x30 cm. A standard layer diet (20% protein and 3.0% calcium) was given ad libitum. Natural daylight was supplemented with artificial light to give an 18-h photoperiod. Eggs were stored at 9-15 degrees C at 70-75% relative humidity in storage room during the remaining period of storage. The eggs were candled on the 6(th) day of incubation to detect fertile eggs and dead embryos. At the end of incubation, unhatched eggs were separated and cracked for determination of the cause including infertile eggs or embryonic mortality. Embryonic mortality rate was calculated as percent of the embryonic deaths within the fertile eggs, not within all death embryos. In this study, overall apparent fertility rate was calculated as 66.5%. The differences between mean apparent fertility rates of the treatment groups were significant (P < 0.01). The lowest hatchability was observed in group 1 (any warming (control group)) (39.9%) while as the highest percentage occurred in groups 4 (warming on day 7 of storage) (56.2%) and 5 (double warming on days 7 and 14 of storage) (57.4%). The hatchability of fertile eggs of group 4 was significantly higher than for groups 1, 2 (warming on day 1 of storage) and 3 (double warming on days 1 and 7 of storage) (P < 0.05). In group 5, the hatchability of fertile eggs was significantly higher than in the other groups (except group 4) (P < 0.05). The highest embryonic mortality rate was observed in early stage of group I while the lowest rate was determined in early stage of group S. Although there was no significant difference in embryonic deaths between groups, effect of pre-incubation warming treatment in decreasing early stage embryonic deaths was observed. Effect of pre-incubation warming in decreasing middle and late stage embryonic deaths was significant. In middle period, the lowest embryonic death rate was seen in group 5 (double warming on days 7 and 14 of storage) while the highest was in group 3 (double warming on days 1 and 7 of storage). In the late period, the lowest embryonic death rate was observed in group 4 (warming on day 7) while the highest was in control group. In the present study, the highest hatching performance and the lowest rate of embryonic deaths (early, middle, and late) were observed in group 5. In control group, however, hatching performance was the lowest and embryonic deaths were the highest. Since there was no significant difference in hatchability between groups warmed on day 7 only and warmed on both days 7 and 14, it can be advantageous to warm eggs on day 7 only to avoid unnecessary expenses in energy and labour.
Keywords: Japanese quail; egg warming; storage; hatching eggs; hatchability; embryonic mortality